Analisis Suku Bunga, Kurs dan Inflasi terhadap Return Saham Blue Chip Sektor Perbankan - Wijayanti, Delia; Sishadiyati, Sishadiyati (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
This study aims to analyze the factors that influence stock returns, especially blue chip stocks in the banking sector. The variables used in this study are interest rates, exchange rates and inflation. This research uses a quantitative approach with multiple linear regression analysis models. The results showed that the variable interest rates, exchange rates and inflation affect the blue chip stock returns of the banking sector. But partially, interest rates do not affect the blue chip stock returns of the banking sector while the exchange rate and inflation affect the blue chip stock returns of the banking sector. This research is very useful for investors in making investment decisions, especially in the banking sector.